Earmarking donations to boost study participation? Evidence from a field experiment - Andreas Raff; Robert Böhm; Christoph Fuchs (PLoS ONE, 2025)
Charitable donations are often the most suitable available way to incentivize study participation, yet their optimal design remains unclear. In a preregistered field experiment, we invited 6,711 psychology faculty at top-200 universities to complete a survey in exchange for a US $5 donation to test whether allowing prospective participants to earmark the donation for a specific purpose increases study participation. Contrary to preregistered hypotheses derived from previous literature, the results showed no significant increase in study participation rates when participants could earmark their donation compared to a random allocation of funds. These findings suggest that while earmarking has been shown to enhance overall donation rates, its effectiveness may not extend to incentivizing study participation.